COPING BEHAVIOR APARATUR PELAYANAN PUBLIK (STUDI PROFESI BIDAN PUSAT KESEHATAN MASYARAKAT DI KOTA BENGKULU) - Alexsander Alexsander (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2018)
The Coping Behaviour of Street Level Bureaucrat (Research on the Midwife Profession of Public Health Units in Bengkulu City). Since the surveys on public service delivery result provided by Public Provision Units in Bengkulu City remains low indeks for years and the problem of behavior of Street Level Bureaucrat is hypothetically become the major cause. The first step of research is aimed to identify what behavior in service delivering done by them. The research is focused on coping behavior of midwife in public health unit or UPTD Puskesmas of Bengkulu City. Research has been done by involving midwife, IBI, Government (Health Disctric Institution of Kota Bengkulu) and Public figures concerning in public health provision together in Focused Group Discussion and continued with ideep Interview. The result shows that limitation of time service and limitation of area service were done to rasionalised the service. The Limitation of Source is done in the way of drugs limitation and asking patience to use herbs, beside maximalizing the internship students in helping patience. To increase patience trust, the midwife implement standard operation procedures with regular time. Simplification is also done in the form of modifying the skills and motion in service providing, the modification is done in emergency situation. The recommendation of the article is further observation and research to generalize the gathered information.